2010
DOI: 10.1097/acm.0b013e3181eab71b
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Education in U.S. Medical Schools: Latest Update of a National Survey

Abstract: Purpose To quantify the number of required hours of nutrition education at U.S. medical schools and the types of courses in which the instruction was offered, and to compare these results with results from previous surveys. Method The authors distributed to all 127 accredited U.S. medical schools (that were matriculating students at the time of this study) a two-page online survey devised by the Nutrition in Medicine Project at the University of North Carolina at Chapel Hill. From August 2008 through July 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
233
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(257 citation statements)
references
References 19 publications
(20 reference statements)
8
233
0
5
Order By: Relevance
“…Low levels of confidence were reported in areas such as promoting suitable food or nutrition goals, monitoring food consumption, translating the Irish food pyramid into practical advice, and formulating meal plans. Previous studies have similarly shown low confidence in nutrition knowledge and skills [19][20][21][22][23]. It was also clear from the findings that previous nutrition education experiences are important in affecting confidence about nutrition care, with those who reported previous education in nutrition having more confidence in certain areas of their knowledge and skills.…”
Section: Discussionsupporting
confidence: 63%
“…Low levels of confidence were reported in areas such as promoting suitable food or nutrition goals, monitoring food consumption, translating the Irish food pyramid into practical advice, and formulating meal plans. Previous studies have similarly shown low confidence in nutrition knowledge and skills [19][20][21][22][23]. It was also clear from the findings that previous nutrition education experiences are important in affecting confidence about nutrition care, with those who reported previous education in nutrition having more confidence in certain areas of their knowledge and skills.…”
Section: Discussionsupporting
confidence: 63%
“…We also investigated whether students adhered to behaviors consistent with current dietary and exercise guidelines 14,15 and explored potential barriers to adopting a healthy lifestyle. Given the limited exposure of health care professional students to required nutrition curriculum, 13,16 we hypothesized that the dietary practices of pharmacy and medical students in this study would not meet current dietary and lifestyle guidelines, and that lack of time and nutritional knowledge would be the main impediments to healthful habits in these individuals.…”
Section: Introductionmentioning
confidence: 99%
“…(See Supplemental Table 1. ) For the past 2 decades, educators used the concept of number of hours of nutrition instruction for the 4-y period (7,24) and the USMLE step 1 nutrition subscores (10,11,14,25) to evaluate improvement in nutrition education among medical schools in the United States. Although we were only able to identify a little >20 h dedicated to nutrition in the preclerkship years, we observed that most of our nutrition preclerkship curriculum objectives were covered during the 4-y period using CurrMIT as well as students and course directors' feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy People 2010 (2) and the US Preventive Services Task Force (3) have recommended that physicians provide nutritional assessment and counseling to their patients, which should require at least 25 h of nutrition education as part of the standard medical curriculum (4,5). Although physicians recognize deficiencies in nutrition knowledge and a lack of confidence in providing effective counseling (6), a recent survey from the University of North Carolina reported minimal improvements in U.S. medical schools in the past decade (7). As a result, a summit was organized by the American Society for Parenteral and Enteral Nutrition to address the shortage of physician nutrition specialists and nutrition medicine education in US medical schools (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation